Sharing economy: Why the Turkish consumers use Airbnb? - Volkan Yakin; Ayşe İdil Kacar; Canan Ay (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2017)
In recent years, the sharing economy has stimulated the development of entities that have contributed significantly to sustainability through the impact of technological, demographic, and cultural changes observed in society. This research aims to determine the motivation of participation of the Turkish consumers contributing to the sharing economy by using the self-determination theory. For this purpose, a questionnaire was conducted with 160 participants contributing to the sharing economy through the use of Airbnb, which is the most commonly used among sharing economies around the world. Examining the results of the research, it is noted that among the three motivational factors (economic benefit, enjoyment, sustainability) which have a positive effect on attitude, only the level of perceived enjoyment has the highest effect on the attitude and also an effect on the behavior intention.
Keywords: M30; M31; O18; Z30; 650; Sharing economy; Consumer behaviors; Airbnb